Insulin signaling in the hippocampus and amygdala regulates metabolism and neurobehavior - Soto, Marion (Proc Natl Acad Sci U S A, 2019)
Previous studies have shown that insulin and IGF-1 signaling in the brain, especially the hypothalamus, is important for regulation of systemic metabolism. Here, we develop mice in which we have specifically inactivated both insulin receptors (IRs) and IGF-1 receptors (IGF1Rs) in the hippocampus (Hippo-DKO) or central amygdala (CeA-DKO) by stereotaxic delivery of AAV-Cre into IR(lox/lox)/IGF1R(lox/lox) mice. Consequently, both Hippo-DKO and CeA-DKO mice have decreased levels of the GluA1 subunit of glutamate AMPA receptor and display increased anxiety-like behavior, impaired cognition, and metabolic abnormalities, including glucose intolerance. Hippo-DKO mice also display abnormal spatial learning and memory whereas CeA-DKO mice have impaired cold-induced thermogenesis. Thus, insulin/IGF-1 signaling has common roles in the hippocampus and central amygdala, affecting synaptic function, systemic glucose homeostasis, behavior, and cognition. In addition, in the hippocampus, insulin/IGF-1 signaling is important for spatial learning and memory whereas insulin/IGF-1 signaling in the central amygdala controls thermogenesis via regulation of neural circuits innervating interscapular brown adipose tissue.